2008
DOI: 10.2147/ndt.s3990
|View full text |Cite
|
Sign up to set email alerts
|

Clinical presentation of anxiety among patients with epilepsy

Abstract: Different factors have been related with interictal anxiety, reported in 10%-25% of patients with epilepsy. We determined the frequency of interictal anxiety in 196 patients with active epilepsy in a cross-sectional survey to know which symptoms of anxiety were most frequently reported in patients with epilepsy and to analyze the factors associated with their presence. Patients were assessed with the Beck Depression Inventory (BDI), MontgomeryAsberg Depression Rating Scale (MADRS), and the Hamilton Anxiety Sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 24 publications
1
17
0
Order By: Relevance
“…These figures are somewhat higher than the 20.5% reported in a sample of 515 patients with epilepsy. 18 Another study using the HAMA, reported a figure of 39% in a sample of 196 patients with epilepsy, 19 a rate similar to our results. Our findings are in line with the majority of the literature; the frequency of anxiety disorders was reported between 15% and 25%.…”
Section: Discussionsupporting
confidence: 90%
“…These figures are somewhat higher than the 20.5% reported in a sample of 515 patients with epilepsy. 18 Another study using the HAMA, reported a figure of 39% in a sample of 196 patients with epilepsy, 19 a rate similar to our results. Our findings are in line with the majority of the literature; the frequency of anxiety disorders was reported between 15% and 25%.…”
Section: Discussionsupporting
confidence: 90%
“…The primary outcome was change from baseline in depressive symptoms, as measured by the rater-administered MADRS [26]. While a variety of standardized tools are used to measure depression in epilepsy, [2729] the MADRS has been used in recent large cross-sectional and longitudinal studies of people with epilepsy. [30, 31] Secondary outcomes included the Brief Psychiatric Rating Scale (BPRS)[32] for global psychiatric symptoms and the Patient Health Questionnaire (PHQ-9) for self-rated assessment of depressive symptoms [33].…”
Section: Methodsmentioning
confidence: 99%
“…Lopez-Gomez and colleagues (7) conducted a cross-sectional survey in all consecutive outpatients with epilepsy who attended the National Institute of Neurology of Mexico between September 2006 and March 2007 and found that 38.8% had symptoms of anxiety. Rai et al (1) found that general anxiety disorders were the most common anxiety disorder with 12.5% of people with epilepsy reporting this condition.…”
Section: Introductionmentioning
confidence: 99%